Analysis of the possibility of implementing recycling water supply systems in meat processing enterprises - Sekirina, Alexandra; Misiuchenka, Viktoryia (Journal of the Belarusian State University. Ecology, 2024)
The article presents an analysis of the water balance of meat processing enterprises of the Republic of Belarus at individual stages of the technological process based on the existing experience in developing individual technological standards for water use. Enterprises were selected based on the volume of processed raw materials, over 50,000 tons of poultry meat and 20,000 tons of cattle and pig meat, located in different regions of the Republic of Belarus. It has been determined that the water consumption standard for technological needs in the processing of poultry meat is higher than in the production of products from the meat of farm animals, while the irretrievable water consumption of enterprises of the first group reaches 80 %, and in the processing of cattle and pig meat up to 30 % of the total water consumption. It has been established that at all stages of the technological process, in accordance with the sanitary standards for meat processing enterprises of various types, drinking water is used. Having passed any of the stages of the technological process, the water is discharged into the enterprise’s sewerage network and then the wastewater enters the treatment facilities of the enterprise or populated area. At different stages of the process, water has different component composition and concentrations of contaminants, for example, at the stages of slaughter and meat processing, it is contaminated with various chemicals, contaminants of biological origin (blood and fats) and pathogenic microorganisms. For the recycling water supply system, it is proposed to return water from the stage of cooling the finished product that does not have contact with the product (about 45 % of the total water consumption for cooling the product). Calculation of the implementation of a recycling water supply system for an enterprise producing cattle meat products showed that water consumption will decrease by 16 % and the volume of wastewater will decrease by 22.3 %. At the same time, when processing poultry meat, these figures are significantly lower – 0.7 % savings in drinking water quality and a reduction in wastewater volumes by 1.52 %.
Keywords: balance of water consumption and water disposal; regulatory requirements; irretrievable water losses; recycling water supply; individual technological standards for water use